ANALISIS KEMANDIRIAN KEUANGAN KABUPATEN DAN KOTA DI PROVINSI NUSA TENGGARA TIMUR TAHUN ANGGARAN 2016-2020 - Nasly Betsyeba Mahalia Loni; Yohana Febiani Angi; Cicilia A. Tungga (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2022)
This study aims to identify and explain the financial independence of districts and cities in East Nusa Tenggara Province based on financial independence ratio analysis with a quantitative descriptive approach. Data collection was carried out using the documentation method, namely by taking financial data in the form of Budget Realization Reports from 22 Regencies/Cities in East Nusa Tenggara Province in 2016-2020. The results of the study show that the level of independence of districts/cities in East Nusa Tenggara Province Not independent has not even touched half of the highest level of independence, in 2016 the highest independence achieved was the "less" criterion with the highest percentage of independence achieved by Kupang City at 18%, In 2017 the highest independence achieved was the "moderate" criteria, an increase of one level compared to the previous year with the highest percentage of independence achieved by the City of Kupang at 27%, the following year 2018 the highest criteria achieved were the "less" criteria, the highest percentage of independence was achieved by Kupang City is 19%, for 2019 and 2020 the highest criteria achieved are the "medium" criteria achieved by West Manggarai Regency in 2019 by 22% and Kupang City for 2020 by 21%.